2007
DOI: 10.1111/j.1365-2672.2007.03428.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fungal culture filtrate containing chitinase as a biocontrol agent against Helicoverpa armigera

Abstract: Aims:  To evaluate the biocontrol efficacy of culture filtrate containing chitinase from Trichoderma harzianum against Heliothis. Methods and Results:  T. harzianum was cultured by submerged fermentation using colloidal chitin as sole carbon source. The ability of the culture filtrate to hydrolyse colloidal chitin indicated the presence of chitinase as one of its components. Biocontrol assay on Heliothis showed that the culture filtrate is a potent antifeedant as it reduced the feeding rate and body weight of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 26 publications
(26 reference statements)
4
39
0
5
Order By: Relevance
“…There are no reports available on use of insect chitinase against Helicoverpa armigera for insecticidal activity but against some other insects has been reported by Binod et al (2007) have reported no mortality by oral delivery of chitinase, but have observed a decrease in weight gain in the test insect larvae similar to the present study. Insect gut enzymes are known to degrade the toxic substances entering their body through diet, a defensive mechanism evolved over a period of time.…”
Section: Respectively and Have The Consensus Sequences Motif I-kxx(supporting
confidence: 80%
See 1 more Smart Citation
“…There are no reports available on use of insect chitinase against Helicoverpa armigera for insecticidal activity but against some other insects has been reported by Binod et al (2007) have reported no mortality by oral delivery of chitinase, but have observed a decrease in weight gain in the test insect larvae similar to the present study. Insect gut enzymes are known to degrade the toxic substances entering their body through diet, a defensive mechanism evolved over a period of time.…”
Section: Respectively and Have The Consensus Sequences Motif I-kxx(supporting
confidence: 80%
“…On the other hand the destruction of peritrophic membrane of the gut by the chitinase might have decreased the feeding efficiency of the larvae resulting in slow growth. Binod et al (2007) recorded 75% mortality on topical application of chitinase on H. armigera larvae whereas in the present study about 40% of them were malformed. Malformed pupae with topical application are indicating chitinase toxicity.…”
Section: Respectively and Have The Consensus Sequences Motif I-kxx(mentioning
confidence: 49%
“…As these enzymes degrade chitin, it might be speculated that these enzymes can cause disruption of cuticle which subsequently causes abnormal molting. Similarly, if these enzymes enter the gut of insect larvae, they can cause significant damage to the peritrophic membrane structure which will result in the larvae being not able to feed and consequently leads to death (Binod et al 2007). This projects that the cocktail of enzymes is a potential agent to be included in the spraying type of biological control agents, provided that the enzymes remain stable for sufficiently longer duration in the environment with retention of activity.…”
Section: Introductionmentioning
confidence: 98%
“…B. thuringiensis takes 3-4 days and NPV (nucleopolyhedrosis viruses) 5-7 days for effective control of insect pests . The studies conducted for testing the efficacy of chitinase as a biocontrol agent against the insect pest H. armigera have shown that the enzyme is capable of negatively affecting the growth and metamorphosis of the larvae (Binod et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Chitinase enzyme solutions having 1000 U/ mL chitinase activity were prepared from His-taq purified enzymes (Binod et al, 2007). Disks of 5 mm dimensions were made from small leaves and were dipped in enzyme preparation for 1 min.…”
Section: Insecticidal Activitiesmentioning
confidence: 99%